A knowledge and attitude of school teachers towards learning disabilities in Bishnupur district, Manipur: a cross sectional study - Asok, Anaswara S.; Akoijam, Pooja; Gupta, Avantika; Akoijam, Brogen Singh (International Journal Of Community Medicine And Public Health, 2021)
Background: Learning problems significantly interfere with academic activities that require reading, mathematical or writing skills. In India 10-14% of children have specific learning disability. The teacher with adequate knowledge of learning disabilities and skills or competencies can do better justice to the children than teacher with general pedagogy backgrounds. The study aimed to assess the teacher’s knowledge and attitude towards learning disabilities and to determine the association between knowledge and attitude with their background characteristics. Methods: A cross sectional study was conducted among 181 teachers of both government and private schools of Bishnupur. Data collected using self-administered questionnaires assessing the knowledge and attitude. Data entered in IBM SPSS 21. Data was expressed using descriptive statistics like frequencies and percentages. Chi-square test was used to check significance between proportions. Results: Data was collected from 181 teachers. Mean age of participants was 42.7±1 and 59.1% of them worked in govt. schools and 40.9% in private. 48.1% of them had adequate knowledge on learning disabilities. Majority (93.9%) had favourable attitude. Association between type of school the teachers taught and knowledge was found to be significant (p<0.05). There was no significant association between attitude with any of the socio-demographic variables. Conclusions: More than half of the teachers had inadequate knowledge on learning disabilities while majority of them had favourable attitude. Teachers belonging to govt. schools had better knowledge on learning disabilities.